2010
DOI: 10.1186/1471-2377-10-105
|View full text |Cite
|
Sign up to set email alerts
|

A seasonal periodicity in relapses of multiple sclerosis? A single-center, population-based, preliminary study conducted in Bologna, Italy

Abstract: BackgroundTemporal, i.e., 24-hour, weekly, and seasonal patterns in the occurrence of acute cardiovascular and cerebrovascular events are well documented; however, little is known about temporal, especially seasonal, variation in multiple sclerosis (MS) and its relapses. This study investigated, by means of a validated chronobiological method, whether severe relapses of MS, ones requiring medical specialty consultation, display seasonal differences, and whether they are linked with seasonal differences in loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 32 publications
0
27
0
3
Order By: Relevance
“…The relative humidity has one period with values below average, justified by the fact that the years 2013/2014 were the driest registered since 1995 in São Paulo 23 . It is observed that hospital admissions have a negative tendency in the studied period, just as the PM 10 . The seasonal component appears in all series; however, as expected, this component is more relevant to explain the temperature behavior.…”
Section: Resultsmentioning
confidence: 75%
See 4 more Smart Citations
“…The relative humidity has one period with values below average, justified by the fact that the years 2013/2014 were the driest registered since 1995 in São Paulo 23 . It is observed that hospital admissions have a negative tendency in the studied period, just as the PM 10 . The seasonal component appears in all series; however, as expected, this component is more relevant to explain the temperature behavior.…”
Section: Resultsmentioning
confidence: 75%
“…There are no studies that report the cause of the decrease in hospitalizations; however, since hospitalizations and PM 10 have the same trend in the study period, it can be inferred that these two variables are related in some way. To investigate a possible relation between them, Table 2 presents the results obtained from the Pearson correlation test among the meteorological variables (Temp.= air temperature; Humid.= relative humidity), PM 10 , and the number of hospital admissions (total, by age and gender).…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations